2013
DOI: 10.1002/grl.50907
|View full text |Cite
|
Sign up to set email alerts
|

Seismic interferometry with antipodal station pairs

Abstract: [1] In this study, we analyze continuous data from all Global Seismographic Network stations between year 2000 and 2009 and demonstrate that several body wave phases (e.g., PP, PcPPKP, SKSP, and PPS) propagating between nearly antipodal station pairs can be clearly observed without array stacking using the noise/coda cross-correlation method. Based on temporal correlations with global seismicity, we show that the observed body waves are clearly earthquake related. Moreover, based on single-earthquake analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 21 publications
2
44
1
Order By: Relevance
“…In this study we apply earthquake coda interferometry techniques [ Lin et al ., ; Lin and Tsai , ; Wang et al ., ] to 1846 USArray stations deployed across North America from January 2004 through September 2013 (Figure b) to extract differential travel times of PKIKP 2 and PKIIKP 2 . Its dense station spacing, high quality recordings (e.g., uniform instrumentation), and especially its wide aperture make USArray an ideal network to probe the deep Earth with seismic interferometry.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we apply earthquake coda interferometry techniques [ Lin et al ., ; Lin and Tsai , ; Wang et al ., ] to 1846 USArray stations deployed across North America from January 2004 through September 2013 (Figure b) to extract differential travel times of PKIKP 2 and PKIIKP 2 . Its dense station spacing, high quality recordings (e.g., uniform instrumentation), and especially its wide aperture make USArray an ideal network to probe the deep Earth with seismic interferometry.…”
Section: Introductionmentioning
confidence: 99%
“…Ruigrok et al () used distant earthquake reverberations to conduct imaging across a 2‐D array in the United States. Lin and Tsai () used antipodal station pairs to extract global body wave phases by cross‐correlating noise and earthquake coda. Boué et al () retrieved deep seismic phases by correlating continuous broadband records containing seismic ambient noise and coda waves exploiting reverberation and scattering.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies networks with dozens of stations were used for stacking to obtain signals of sufficient quality. Lin and Tsai [] showed that the recovery of teleseismic body waves traveling between antipodal stations is effective for sequences of seismic records that contain large earthquakes. This allowed for the retrieval of body waves traversing the Earth between individual stations, which suggests that the nature of the wavefield excited by large earthquakes is better suited for the retrieval of teleseismic body waves than ambient seismic noise.…”
Section: Introductionmentioning
confidence: 99%